Off-line coupling of capillary electrophoresis to substrate-assisted laser desorption inductively coupled plasma mass spectrometry - Pes, Ondrej; Jungová, Pavla; Vyhnánek, Radek; Vaculovic, Tomás; Kanický, Viktor; Preisler, Jan (Analytical chemistry, 2008)
A novel off-line coupling of capillary electrophoresis (CE) and inductively coupled plasma mass spectrometry (ICPMS) is reported here. The coupling interface is based on the connection of a separation capillary to a deposition capillary via a liquid junction maintaining high separation efficiency and sample utilization due to the self-focusing effect and lack of pressure-induced flow in comparison with nebulizer-like interfaces. The separation is recorded in the form of droplets of CE effluent on a suitable substrate--a poly(ethylene terephthalate) glycol (PETG) sample plate placed inside a partially evacuated chamber. Substrate-assisted laser desorption (SALD) is used to vaporize the sample fractions and to enable further transfer to the ICPMS. The mechanism of SALD is examined using model samples deposited on a variety of substrates. The highest response is obtained for a PETG substrate; sample desorption due to ablation of PETG is found to outweigh direct ablation of sample. Detection limits are given for several metal elements. Finally, a rapid (2.5-min), high-resolution separation of Cr(III)/Cr(VI) species injected in subpicomolar quantity is shown.